Foot Embolization During Limb Salvage Procedures in Critical Limb Ischemia Patients Successfully Managed With Mechanical Thromboaspiration: A Technical Note. (August 2015) - Gandini, Roberto; Merolla, Stefano; Chegai, Fabrizio; Del Giudice, Costantino; Stefanini, Matteo; Pampana, Enrico
Purpose: To illustrate the use of a mechanical thromboaspiration device originally designed for clot retrieval in acute stroke in the treatment of acute distal embolism occurring during percutaneous revascularization of the femoropopliteal and below-the-knee arterial segments.Technique: The Penumbra system was adapted for aspiration of thrombus in the distal foot arteries as a standalone device. The 2 over-the-wire, tapered lumen catheters have long working lengths (139 cm for the 4MAX to 153 cm for the 3MAX) that allow advancement below the ankle even with a retrograde contralateral approach. Once the occluded arterial segment is reached, the catheters are connected to the dedicated pump for continuous vacuum aspiration. The use of the device is illustrated in 3 diabetic patients (1 woman and 2 men; ages 88, 70, and 73 years, respectively) undergoing limb salvage procedures who experienced distal embolization that would have seriously jeopardized the foot circulation. The lumens of the occluded arteries were restored without complication.Conclusion: While further evaluation in a larger cohort of patients is needed, this initial experience using the Penumbra system in the peripheral vasculature suggests that this is a rapid, effective approach to address intraprocedural foot embolization and avoid possible grave clinical sequelae.